PENTINGNYA TEKNIK INVENTION DALAM PRATULIS - Purba, Andiopenta (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
In the process of writing an essay there are three steps that must be prepared and implemented, the third stage is prawrite, writing, and editing. In prawrite, one of the steps that must be done is invention. Invention is a technique of thinking and find ways to express and convey ideas to cultivate and develop the subject matter in writing. Invention as a writing technique consists of various types, ie: brainstorming, reflection, journalistic formula of five "W" one "H", the four questions in classical rhetoric, and problem solving. Each type of invention has strengths and weaknesses, so a writer must be wise in choosing the type of inventionÂ used. Keywords: technique invention, process of writing